2019
DOI: 10.1109/access.2019.2941712
|View full text |Cite
|
Sign up to set email alerts
|

Design and Control of a Dual-Stage Actuation Active Vibration Isolation System

Abstract: Active vibration isolation system is used in various fields to reduce the vibrations transmitted. In this paper, a novel dual-stage actuator is proposed, which combines a voice coil motor and a piezoelectric actuator. The proposed dual-stage actuator maintains the advantages, in terms of the long stroke, the high precision, and the wide band. The dual-stage actuation active vibration isolation system (DSA-AVIS) with the proposed dual-stage actuator is initially modeled. The characteristic of the DSA-AVIS is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…According to the proposed dynamic model, the function of the active vibration isolation system based on the piezoelectric actuator is given in eq and the possible control force that the system will produce is given in eq . Here, ε, E h , δ, c d , ρ, and l give the axial strain, modulus of elasticity, strain due to input voltage, stress, material damping, and length, respectively. Here, F i , A r , x i , r i , and λ i represent the control force, cross-sectional area of the PZT, output displacement, base displacement, and output displacement generated by the voltage, respectively. Zhao et al (2017), developed a dual stage active vibration isolation system, combination of a voice coil motor and piezoelectric actuator . The simulation and experimental results have shown that the proposed si x -axis orthogonal active vibration isolation platform with piezoelectric actuator can effectively reduce the dynamic response of an average of 5 dB payload in the frequency range of 20 Hz to 200 Hz.…”
Section: Civil Engineering Applications Of Piezoelectric Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the proposed dynamic model, the function of the active vibration isolation system based on the piezoelectric actuator is given in eq and the possible control force that the system will produce is given in eq . Here, ε, E h , δ, c d , ρ, and l give the axial strain, modulus of elasticity, strain due to input voltage, stress, material damping, and length, respectively. Here, F i , A r , x i , r i , and λ i represent the control force, cross-sectional area of the PZT, output displacement, base displacement, and output displacement generated by the voltage, respectively. Zhao et al (2017), developed a dual stage active vibration isolation system, combination of a voice coil motor and piezoelectric actuator . The simulation and experimental results have shown that the proposed si x -axis orthogonal active vibration isolation platform with piezoelectric actuator can effectively reduce the dynamic response of an average of 5 dB payload in the frequency range of 20 Hz to 200 Hz.…”
Section: Civil Engineering Applications Of Piezoelectric Materialsmentioning
confidence: 99%
“…Zhao et al ( 2017), developed a dual stage active vibration isolation system, combination of a voice coil motor and piezoelectric actuator. 68 The simulation and experimental results have shown that the proposed six-axis orthogonal active vibration isolation platform with piezoelectric actuator can effectively reduce the dynamic response of an average of 5 dB payload in the frequency range of 20 Hz to 200 Hz. The active vibration isolation system presented in Figure 13, which has long stroke, high sensitivity, and wide band gaps.…”
Section: Structural Control Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the actual system, due to the existence of various noises and unmodeled dynamics, the value of observed states often contains high frequency oscillations, so it is necessary to introduce a low-pass filter for removing its high frequency component. Defining χ as filtered χ, and combining Equation (15) with Equation ( 16), we can obtain the actual disturbance force transmitted by backlash as…”
Section: A Estimation Of Nonlinear Backlash Disturbance Forcementioning
confidence: 99%
“…In terms of control strategy design, the traditional double-loop PID control and its extended methods have been widely used in this kind of motion platform due to its advantages, e.g., no need for modeling, simple design, fewer control parameters and easy adjustment, etc., and it can generally help systems achieve the specified motion accuracy under no-disturbance working conditions [11][12][13]. The control strategies based on frequency-domain analysis could suppress various coupling vibrations by expanding the system bandwidth, which optimizes the dynamic characteristics of platforms [14][15][16]. Nowadays, various modern control strategies, such as predictive control, sliding mode control, internal model control and active disturbance rejection control, have also been gradually applied in such platforms to comprehensively improve both their dynamic performance and positioning accuracy from the angles of convex optimization, nonlinear feedforward and disturbance robustness enhancement [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%